Human-interpretable clustering of short text using large language models - Justin K. Miller; Tristram J. Alexander (Royal Society Open Science)
Clustering short text is a difficult problem, owing to the low word co-occurrence between short text documents. This work shows that large language models (LLMs) can overcome the limitations of traditional clustering approaches by generating embeddings that capture the semantic nuances of short text. In this study, clusters are found in the embedding space using Gaussian mixture modelling. The resulting clusters are found to be more distinctive and more human-interpretable than clusters produced using the popular methods of doc2vec and latent Dirichlet allocation. The success of the clustering approach is quantified using human reviewers and through the use of a generative LLM. The generative LLM shows good agreement with the human reviewers and is suggested as a means to bridge the ‘validation gap’ which often exists between cluster production and cluster interpretation. The comparison between LLM coding and human coding reveals intrinsic biases in each, challenging the conventional reliance on human coding as the definitive standard for cluster validation.